2018 16th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks (WiOpt) 2018
DOI: 10.23919/wiopt.2018.8362859
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-based wireless energy transfer for low complex energy receivers

Abstract: This paper proposes a novel channel estimation method and a cluster-based opportunistic scheduling policy, for a wireless energy transfer (WET) system consisting of multiple low-complex energy receivers (ERs) with limited processing capabilities. Firstly, in the training stage, the energy transmitter (ET) obtains a set of Received Signal Strength Indicator (RSSI) feedback values from all ERs, and these values are used to estimate the channels between the ET and all ERs. Next, based on the channel estimates, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Satisfying the constraints will be comparatively easier as well when the two ERs are closer to each other, and hence, the infeasible region is expected to shrink when the number of ERs increases. An extension that stems on the idea presented in this paper on scheduling ERs that are closer to each other in terms of their channel phase can be found in [21].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Satisfying the constraints will be comparatively easier as well when the two ERs are closer to each other, and hence, the infeasible region is expected to shrink when the number of ERs increases. An extension that stems on the idea presented in this paper on scheduling ERs that are closer to each other in terms of their channel phase can be found in [21].…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The accuracy of the CSI estimation for WET has thus been investigated in [3], [16], [23][24][25][26][27][28].…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…The authors optimize the size of the training codebook for channel acquisition to balance the trade-off between channel estimation precision and energy transmission time. These results are extended to multiple single-antenna energy receivers in [26]. Based on the feedback, the transmitter employs a maximum likelihood channel estimation method and clusters the receivers according to their channel phases during energy transmission.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…Further, the efficacy of received signal strength indicator (RSSI) feedback values based CE protocols has been lately investigated in [19], [20]. However, these fully-digital EBF works [14]- [20] adopted an overly simplified linear rectification model for their investigation, which has been recently [21]- [26] shown to perform poorly for the practical RF EH circuits. The detailed investigation on RF EH performance using the statistical CSI as conducted in [25], [26] suggested that for an accurate characterization, a nonlinear EH model should be adopted during investigations.…”
Section: A State-of-the-artmentioning
confidence: 99%
“…InFig. 2, we plotted the linear model which is most commonly adopted due to its analytical simplicity[14]-[20]. Whereas, we have considered a more generic PWLA model[23] in place of CL (having L = 2) and CLC (i.e., L = 3) models.…”
mentioning
confidence: 99%